Finanças comportamentais: uma análise das exigências de prêmio pelos alunos de Economia da UFPB. - Alves, Willemberg Harley de Lima (2009)
The Theory of Behavior Finance shows an approach that faces the Modern Theory of Finance, when considering some features such as psychology, emotional and social, that make the decisions of the economic agents. Regarding to the decisions based on whether rational or cognitive foundations, this work aims at analyzing, through a descriptive research, the prize expectation by the pupils of Economics at UFPB. The research population was classified into four major groups, concerning to the knowledge of Finance and Financial Market and each group counts of 20 students. A questionnaire was accomplished to collect the data. The main results points out that in average the students who have less knowledge about the financial market are those who also have lower risk behave and that the groups have different perception of risk measurement. Also, it can be pointed out that the different perception of the risk makes the difference of prize exigencies by the pupils and that the dispersion of the exigencies is smaller as the knowledge of the risk is stronger.